MyRELASIS UTHM Digital ePortal: Development of RELASIS Student Information System - HALIM, SITI NOORMASHETAH; Mohamad, Radiah (Applied Information Technology And Computer Science, 2025)
In the modern age of Information and Communication Technology (ICT), office management has evolved to become more efficient through technological advancements. However, the Briged RELA Siswa Siswi (RELASIS) UTHM still relies on manual methods to manage student information and office documents, leading to inefficiencies and data tracking challenges. This project aims to address these issues by developing the MyRELASIS UTHM Digital ePortal system, a web-based platform that streamlines student information management, report generation, and office operations. In addition, the system’s objectives include designing and developing the system and testing it with the target users, which involves administrators, instructors, and students. The system’s modules include login and registration, order, order management, activities record, user profile and report module generation. By implementing this system, the project initiatives to reduce reliance on manual methods, enhance efficiency, and provide secure data storage. Not only that, improve accessibility and facilitates rapid information retrieval for comprehensive reporting. The chosen methodology for this project is the Prototype model, which includes iterative development, user feedback and continuous improvement. The project is important because it will help offices become more efficient while cutting down on paper use and raising productivity. This project provides a revolutionary approach to update RELASIS’s student information management system in line with the rapidly changing digital environment.